1999
DOI: 10.1128/aac.43.8.2046
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea Enhances the Activities of Didanosine, 9-[2-(Phosphonylmethoxy)ethyl]adenine, and 9-[2-(Phosphonylmethoxy)propyl]adenine against Drug-Susceptible and Drug-Resistant Human Immunodeficiency Virus Isolates

Abstract: We assessed the effects of hydroxyurea (HU) at a concentration of 50 μM on the in vitro activities of 2′,3′-dideoxyinosine (ddI), 9-[2-(phosphonylmethoxy)ethyl]adenine (PMEA), and 9-[2-(phosphonylmethoxy)propyl]adenine (PMPA) against a wild-type human immunodeficiency virus (HIV) type 1 (HIV-1) laboratory isolate and a panel of five well-characterized drug-resistant HIV isolates. Fifty micromolar HU significantly increased the activities of ddI, PMEA, and PMPA against both the wild-type and the drug-resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…The addition of 50µM hydroxyurea decreased the IC 50 of didanosine for both didanosine resistant clones to levels comparable to those obtained with wild type strains in the absence of hydroxyurea. Similar results were obtained by an independent group [31]. Thus, decreasing the level of dATP, the cellular competitor of didanosine, favored the incorporation of didanosine even though the viral reverse transcriptase was resistant to this nucleoside analog.…”
Section: Profile Of Hydroxyurea-didanosine Combinationsupporting
confidence: 87%
“…The addition of 50µM hydroxyurea decreased the IC 50 of didanosine for both didanosine resistant clones to levels comparable to those obtained with wild type strains in the absence of hydroxyurea. Similar results were obtained by an independent group [31]. Thus, decreasing the level of dATP, the cellular competitor of didanosine, favored the incorporation of didanosine even though the viral reverse transcriptase was resistant to this nucleoside analog.…”
Section: Profile Of Hydroxyurea-didanosine Combinationsupporting
confidence: 87%
“…In fact, for HSV-1, the potentiating effect of hydroxyurea on PMEA was relatively weak. In a recent study, Palmer and colleagues (26) demonstrated that PMEA and hydroxyurea synergistically inhibit the replication of wild-type and drug-resistant HIV. We do not yet have an explanation of why the antiherpesvirus activity of PMEA is less potentiated by hydroxyurea than those of other nucleoside analogs, the active metabolites of which do not, unlike PMEA, compete with dATP in the (viral) DNA polymerization process.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxyurea has been used for many years for the treatment of a variety of neoplasms (10) and appears, in addition, to offer clinical benefit for the treatment of sickle cell anemia (4). Hydroxyurea has been shown to inhibit the replication of human immunodeficiency virus (HIV) type 1 (HIV-1) (16) and to potentiate the anti-HIV activities of several 2Ј,3Ј-dideoxynucleoside analogs, in particular, didanosine (ddI) (12-14, 18, 25), as well as those of the nucleoside phosphonate analogs adefovir [9-(2phosphonylmethoxyethyl)adenine (PMEA)] and tenofovir [9-(2-phosphonymethoxypropyl)adenine (PMPA)] (26). The precise mechanism responsible for this potentiation has not been elucidated, but it is conceivable that the depletion of the intracellular 2Ј-deoxynucleoside 5Ј-triphosphate (dNTP) pools induced by hydroxyurea results in a decreased competition of the triphosphate metabolites of the antivirally active nucleoside analogs with the natural dNTP substrate at the level of the reverse transcriptase of HIV.…”
mentioning
confidence: 99%
“…In vitro, concentrations of hydroxyurea similar to those attained in vivo decreased the IC 50 of tenofovir in several recombinant HIV isolates, including those with the K65R mutation. 60 However, in a substudy of study 901, hydroxyurea 500 mg twice/day did not significantly enhance the antiviral activity of low-dose (i.e., 75 mg) tenofovir relative to tenofovir monotherapy. 61 Furthermore, the initial optimism surrounding hydroxyurea as a means of augmenting the activity of didanosine and overcoming didanosine resistance was tempered by later results suggesting a lack of virologic gain with hydroxyurea relative to placebo at the expense of greater toxicity (i.e., pancreatitis, peripheral neuropathy).…”
Section: Pharmacodynamicsmentioning
confidence: 95%